2010
DOI: 10.4102/td.v6i2.263
|View full text |Cite
|
Sign up to set email alerts
|

New Public Management, science policy and the orchestration of university research – academic science the loser

Abstract: In many countries - during the past three decades - there has been increasing alignment of public administration with neoliberal modes of governance driven by processes of globalization and privatization. Key is New Public Management (NPM) as an instrument for applying private sector or market-based techniques to public services. The paper concerns the implications and impact of these developments as they relate to the university sector where we are seeing an influx of bibliometrics to assess performativity wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…Ahora bien, estas consideraciones relativas a los impactos y beneficios esperados -sean de un tipo u otro -, encierran un debate sobre los criterios de calidad y los valores en relación con la ciencia, muy unido a los propósitos que rigen y prescriben la profesión académica (Elzinga, 2010), que oscila entre una concepción de la universidad cuyo principal énfasis está en la independencia de la investigación académica con el objetivo de "generación de conocimiento por su propio bien", y otra que asocia el rol de la universidad a ser una fuente de conocimiento para el desarrollo económico y social. A ello se une que, los valores del investigador en relación con la ciencia, que están afectados por el uso generalizado de los indicadores métricos y la diversificación de los resultados esperados, difieren de la perspectiva sociológica clásica, según el cual, "el objetivo institucional de la ciencia es la extensión del conocimiento certificado" (Merton, 1973(Merton, [1942: 270).…”
Section: La Diversificación De Los Indicadores De Resultadosunclassified
“…Ahora bien, estas consideraciones relativas a los impactos y beneficios esperados -sean de un tipo u otro -, encierran un debate sobre los criterios de calidad y los valores en relación con la ciencia, muy unido a los propósitos que rigen y prescriben la profesión académica (Elzinga, 2010), que oscila entre una concepción de la universidad cuyo principal énfasis está en la independencia de la investigación académica con el objetivo de "generación de conocimiento por su propio bien", y otra que asocia el rol de la universidad a ser una fuente de conocimiento para el desarrollo económico y social. A ello se une que, los valores del investigador en relación con la ciencia, que están afectados por el uso generalizado de los indicadores métricos y la diversificación de los resultados esperados, difieren de la perspectiva sociológica clásica, según el cual, "el objetivo institucional de la ciencia es la extensión del conocimiento certificado" (Merton, 1973(Merton, [1942: 270).…”
Section: La Diversificación De Los Indicadores De Resultadosunclassified
“…EU), and global (Shapira et al, 2001;Perry & May, 2007;Laranja et al, 2008;Langfeldt et al, 2012);  the rise of 'new public management' with its demands for public accountability, e.g. in the form of performance indicators (Elzinga, 2010(Elzinga, & 2012Doern & Stoney, 2009a);  efforts to raise the level of public engagement -there have been growing demands for greater public involvement in issues relating to science and technology, in particular where there are historical sensitivities or an element of 'risk' is perceived to be involved (Jacob, 2005);  initiatives responding to 'Grand Challenges' -since these are global in nature and also cross-cut other traditional boundaries (e.g. those of government ministries), R&D policy needs to be integrated within a much broader array of policies (Cagnin et al, 2012).…”
Section: From National To Multi-level Governancementioning
confidence: 99%
“…Within this context, it was observed that some of the NPM principles could be extended to the domain of scientific policy in some countries along with market logic related to efficiency, results-based management, entrepreneurship and partnerships, and this began to be incorporated in the academic discourse in terms of science and technology policies (ELZINGA, 2010). In other words, the global transformations associated with manifestations of NPM extended to the institutional context of the production of knowledge, which became capitalized (ETZKOWITZ and LEYDESDORFF, 2000) or merchandized -as other authors preferred to define it (ARMBRUSTER, 2008;ELZINGA, 2010), creating a debate full of antagonistic positions in the scientific realm.…”
Section: Introductionmentioning
confidence: 99%